The Struggle between the Patricians and the Plebeians during the Roman Republic - Bruscas López, Javier (Revista de derecho aragonés, 2025)
The patrician-plebeian conflict in ancient Rome had its origin in the marked disparity between two clearly differentiated social classes. At the top were the patricians, an elite with privileges and rights superior to the rest of the population, whose members monopolized political, military and social power. Below them were the plebeians, marginalized, who with their effort and work contributed a crucial role to the prosperity of Rome and, in return, were rewarded with injustice, distance and oblivion. The patrician-plebeian struggle lasted for more than two hundred years, and we can situate the development of the dispute mainly throughout the Republican period of Rome, from the Servian Reform, implemented by King Servius Tullius between 578 BC and 534 BC, until the promulgation of the lex Hortensia in 287 BC.